Modern farm power - Promersberger, William J.; Priebe, Donald W.; Bishop, Frank E. (Reston, Va. : Reston Pub. Co., 1979)
There have been a great number of very important changes in technology. Many of these significant development have taken place in the field of farm power and closely related areas. Such progress and change pose a greater need for a thorough understanding of internal combustion engines and allied equipment and accessories in the field of farm power hence the need for the revision.
Includes bibliographies and index.
occ 17/01/2019
Loans
Keywords: Farm engines; Farm tractors; Farm mechanization